Lymphatic Leak After Intestinal Transplantation: Aspects of the Donor Technique. (December 2017) - Girlanda, Raffaele; Desai, Chirag; Matsumoto, Cal; Fishbein, Thomas
The rich component of lymphatics makes the intestine prone to leaks of lymph after transplantation secondary to their transection during procurement. We describe our technique for isolation and ligation of the small lymphatics at the root of the mesentery during the procurement of the small intestine and report our experience with the management of lymphatic leaks posttransplant.